The economic development of Japan, 1868-1941 - Macpherson, W. J.; Economic History Society (Cambridge ; New York, NY, USA : Cambridge University Press, 1995)
This book provides an incisive overview of Japanese economic history between 1868 and 1941. It introduces and surveys the current state of scholarship on Japan, touching upon almost all elements of the Japanese historical experience. A select bibliography (now updated to 1994) is provided, to help the reader pursue the subject in more detail
Includes bibliographical references and index.
Keywords: Japan -- Economic conditions